Menelusuri Nilai-Nilai Nasionalisme dalam “Peringatan Malam Tasyakuran Kemerdekaan”: Studi Etnografi dalam Kegiatan Keagamaan - Ahmala, Majidatun (Koordinatorat Perguruan Tinggi Keagamaan Islam Swasta Wilayah IV Surabaya, 2024)
Indonesian people hold various activities to celebrate the independence of Republic of Indonesia. One of the activities was a night of thanksgiving which was held the day before August 17 by tthe community of neighborhood. The aim of this research is to explore depthly about the values of nationalism from the routine activities every night of independence day. This reseach uses participator ethnographic methods with researches who are actively involved in commmitte activities that build of close relationships with the community. This reseach was cinducted in Plumbungan village, specifically rt.03 rw.01, Sukodono-Sidoarjo. Observation and participation of researchers while interacting with the community becomes a technique for collecting data. The results of this research show that the nationalist valuwes found are: the value of love for homeland is based on hubbul wathan minal iman, the value of unity and oneness which is represented through thanksgiving, the value of service to the country through the participation of all citizens in events, the values of toleranace by emphasizing the princple of ukhuwah islamiyah